UU P2SK DAN PENGARUHNYA TERHADAP MODEL PENGAWASAN OJK: TWIN PEAKS SEBUAH ALTERNATIF - Agus Riyanto; Budi Santoso; Paramita Paraningtyas; Rafsi Azzam Hibatullah Albar (Mimbar Hukum, 2023)
Abstract The supervisory journey in the financial sector in Indonesia, which has been going on for approximately 12 years since the emergence of the Financial Services Authority (OJK) has uncovered serious problems. Various problems in the financial sector from banks, insurance, pension funds, capital markets, and so on made the OJK the institution most frequently reported to the Indonesian Ombudsman. The change in model from integration to twin peaks is deemed relevant to adapt to global developments and also the national situation in the future. Therefore, it is hoped that the presence of the P2SK Law can carry out these reforms to strengthen the optimal regulatory and supervisory role of the OJK. Seeing the success of several countries in implementing twin peaks can be used as a consideration to initiate changes to the P2SK Law so as not to allow problems in various sectors to continue to pile up and not be resolved properly and ultimately consumers become victims of the weaknesses in creating good financial institutions. Abstrak Perjalanan pengawasan di sektor keuangan di Indonesia yang telah berlangsung kurang lebih 12 tahun sejak kemunculan Lembaga Otoritas Jasa Keuangan (OJK) menemukan persoalan yang serius. Berbagai persoalan di sektor keuangan dari bank, asuransi, dana pensiun, pasar modal, dan lain sebagainya menjadikan OJK sebagai Lembaga yang paling sering dilaporkan di Ombudsman RI. Perubahan model dari integrasi ke twin peaks dirasa relevan untuk menyesuaikan dengan perkembangan global dan juga situasi nasional kedepannya. Oleh karena itu kehadiran UU P2SK diharapkan bisa melakukan reformasi tersebut untuk memperkuat peran regulasi dan pengawasan yang optimal dari OJK. Melihat keberhasilan beberapa negara dalam menerapkan twin peaks dapat dijadikan pertimbangan untuk memulai perubahan pada UU P2SK agar tidak membiarkan persoalan di berbagai sektor terus menumpuk dan tidak terselesaikan dengan baik dan akhirnya konsumen menjadi korban dari kelemahan penciptaan kelembagaan keuangan yang baik.